Pre-service teachers’ readiness and engagement for online learning during the covid-19 pandemic: A rasch analysis - Laksmiwati, Pasttita Ayu (Springer Science and Business Media Deutschland GmbH, 2022)
The widespread of the COVID-19 pandemic has challenged training institutions to rethink the execution of their training programs. New approaches to teaching and learning are now needed due to the forced shift to e-learning modes. However, questions remain about how ready pre-service teachers are and their level of engagement in an online learning model of instruction. The purpose of this study was to investigate the readiness and engagement of pre-service teachers for online learning in Indonesia. This study used a non-experimental quantitative research design. Data were gathered from a sample of 285 pre-service teachers using a questionnaire. Data were analysed using WINSTEPS Rasch model measurement software version 4.30. Descriptive statistical analysis was used to examine pre-service teachers’ readiness and engagement of pre-service teachers for an online learning model of instruction, and a Differential Item Functioning (DIF) analysis was carried out to specifically assess their readiness and engagement for online learning based on their gender and age. Findings indicate pre-service teachers were not ready for online learning during the Covid-19 Pandemic in Indonesia. However, pre-service teachers were found to be actively engaged in online learning. Further analysis indicated there were differences in pre-service teachers’ readiness and engagement in online learning based on their gender and age. This study provides insight into pre-service teachers towards an online learning model of instruction in Indonesia, discusses implications, and offers recommendations for future research. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.